(untitled) (Medico Legal Update, 2020)
Background: Thoracolumbar burst fracture required to conduct short segment posterior stabilization as the operative therapy. The short segment fixation (above and under fracture level (four-screw pedicle)) encounters loss of correction and failure including progressive kyphosis, screw pedicles and rods that are bent or fractured. Rod around fracture site receives bigger loads than other parts due to its function as cantilever. To overcome this, it uses short-segment posterior stabilization instrumentation in which pedicle screw is installed above, under, and on fracture site level (six-screw pedicle) to increase stiffness. Objective: To analyze the comparison stiffness of four-screw versus six-crew short segment pedicle posterior stabilization instrumentation in cyclic axial compression. Method: This study used in vitro mechanical test in simulation of vertebrae from UHMWPE (Ultra High Molecular Weight Polyethilene) that was fixated with four-screw and six-screw pedicle. Each construction is given cyclic axial compression. Afterwards, the stiffness of each construction was measured. Results: Six-screw short segment pedicle posterior vertebrae stabilization instrumentation had higher stiffness of 43.38% than four-screw short segment pedicle posterior vertebrae stabilization instrumentation in cyclic axial compression. There was a significant difference in both groups (p<0.05) Conclusion: Six-screw short segment pedicle posterior vertebrae stabilization instrumentation was better than four-screw short segment pedicle posterior vertebrae stabilization instrumentation in cyclic axial compression